Northern Ballet Theatre Review - Phillips, Katie (Dance Books Ltd., Alton,Hampshire (UK), 2003)
PALABRAS CLAVE: Northern Ballet Theatre, David Nixon, Wuthering Heights.
Dentro del apartado "Dance Now. Short Takes".